L'enseignement supérieur entre l'économie de la connaissance et les initiatives locales interculturelles - Roser Cussó; Anayansi Gonzalez (Université de Provence, 2017)
The introduction of the principles of the economy of knowledge and the employability in the universities and research seems to be generalized. Nevertheless, the international organizations (IO), main bridges of those principles, do not implement them in the same way; competing one each other, IOs are still relatively different. In contrast with the World Bank, the EU and the OECD, UNESCO takes into account some original local initiatives. It is the case of the intercultural universities. The study of one of these universities in Mexico allows us to contrast the global harmonizing trends with a set of alternative pedagogical proposals. Are the latter carrying new politics and/or values?